Identification of EGFR mutation, KRAS mutation, and ALK gene rearrangement in cytological specimens of primary and metastatic lung adenocarcinoma. Issue 9 (12th March 2013) - Cai, Guoping; Wong, Rebecca; Chhieng, David; Levy, Gillian H.; Gettinger, Scott N.; Herbst, Roy S.; Puchalski, Jonathan T.; Homer, Robert J.; Hui, Pei
<x xml:space="preserve">Abstract</x> BACKGROUND The identification of molecular alterations has an important therapeutic implication in patients with lung adenocarcinomas. In the current study, the authors evaluated their experience with the identification of epidermal growth factor receptor (EGFR), Kirsten rat sarcoma viral oncogene homolog (KRAS) mutation, and anaplastic lymphoma kinase (ALK) gene rearrangement using cytological specimens of primary and metastatic lung adenocarcinoma. METHODS A total of 54 cases of lung adenocarcinomas (11 primary and 43 metastatic tumors) in which molecular tests were performed were retrieved. Molecular tests were performed on the cell block material of 19 effusions and 35 fine‐needle aspirates. EGFR mutation was evaluated by polymerase chain reaction sequencing analysis of exons 18, 19, 20, and 21. KRAS mutation was tested using polymerase chain reaction–single‐strand conformational polymorphism analysis of codons 12 and 13. ALK gene rearrangement was evaluated by fluorescence in situ hybridization using an ALK break apart probe. RESULTS Molecular tests were successful in 49 of 54 cases (91%). Evaluation of EGFR mutation, KRAS mutation, and ALK gene rearrangement were performed in 49 cases, 14 cases, and 22 cases, respectively. EGFR mutations were found in 14 of 49 cases (29%), including 5 primary and 9 metastatic tumors. Three metastatic/recurrent adenocarcinomas demonstrated an additional EGFR T790M mutation that was not identified in the original specimens. KRAS mutation was detected in 3 of 14 cases (21%) including 1 primary and 2 metastatic tumors. ALK gene rearrangement was evident in 3 of 22 cases (14%), all of which were metastatic tumors. CONCLUSIONS The results of the current study have demonstrated the feasibility of using cytological specimens for EGFR mutation, KRAS mutation, and ALK gene rearrangement analysis. Repeating molecular testing in metastatic/recurrent lung adenocarcinomas may uncover newly acquired molecular alterations. Cancer (Cancer Cytopathol) 2013;121:500–7. © 2013 American Cancer Society.